High pressure studies of metal-organic frameworks and coordination complexes - O'Connor, Alice (2017)
High pressure X-ray crystallography is an effective tool for studying the behaviour of systems in the solid state. It is becoming an increasingly popular technique and offers a way to determine and monitor the behaviour of systems, which in some cases is necessary in order for those particular materials to be used in real-world applications. This thesis explores the use of high pressure X-ray crystallography to understand the behaviour of systems such as metal-organic frameworks (Chapters 4and 5) and the coordination complexes, [1,4-C6H4{PPh2(AuCl)}2](Chapter 6) and chloro(4-ethoxycarbonyl-6-phenyl-2,2′-bipyridyl)platinum (Chapter 7). It also describes hydrostatic limit determinations carried out on 4:1 MeOH/EtOH with additional additives such as silicon grease and/or crystals of [PdCl2([9]aneS2O)] to see how the hydrostatic limit might be manipulated by the use of these additives. It has been possible to determine the hydrostatic limit of a possible pressure-transmitting medium, namely RS3000, which showed an increased pressure limit when compared to the hydrostatic limits for other similar media. This thesis therefore covers a wide range of studieshighlighting some of the diversity that this fieldoffers. To betterunderstand the behaviour of the systems studied, several ancillary techniques have been employed including Hirshfeld surface analysis, Raman spectroscopy, UV/visible spectroscopy and theoretical calculations. In all cases these techniques provided useful information which complemented the results of the high pressure X-ray crystallographic studies.